Global koff‐rates of polyclonal T‐cell populations merge subclonal avidities and predict functionality. Issue 4 (13th February 2022) - Lückemeier, Philipp; Molter, Katherine L.; Jarosch, Sebastian; Huppertz, Patrick; Purcarea, Anna; Effenberger, Manuel J. P.; Nauerth, Magdalena; D'Ippolito, Elvira; Schober, Kilian; Busch, Dirk H.
Abstract: The avidity of TCRs for peptide‐major histocompatibility complexes (pMHCs) is a governing factor in how T cells respond to antigen. TCR avidity is generally linked to T‐cell functionality and there is growing evidence for distinct roles of low and high avidity T cells in different phases of immune responses. While physiological immune responses and many therapeutic T‐cell products targeting infections or cancers consist of polyclonal T‐cell populations with a wide range of individual avidities, the role of T‐cell avidity is usually investigated only in monoclonal experimental settings. In this report, we induced polyclonal T‐cell responses with a wide range of avidities toward a model epitope by altered peptide ligands, and benchmarked global avidity of physiological polyclonal populations by investigation of TCR‐pMHC k off ‐rates. We then investigated how varying sizes and avidities of monoclonal subpopulations translate into global koff ‐rates. Global k off ‐rates integrate subclonal avidities in a predictably weighted manner and robustly correlate with the functionality of murine polyclonal T‐cell populations in vitro and in vivo. Surveying the full avidity spectrum is essential to accurately assess polyclonal immune responses and inform the design of polyclonal T‐cell therapeutics. Abstract : Little is known about polyclonal T‐cell populations' TCR‐ligand avidity and how it relates to functionality. We assess TCR‐ligand k off ‐rates ex vivo and establish a positive correlation with functional parameters. Defined polyclonal populations from monoclonal T cells reveal predictability of global koff ‐rates, informing the design of T‐cell products.